Design of an efficient combined multipoint picking scheme for tea buds - Xu, Lijia; Xie, Yi; Chen, Xinyuan; Chen, Yanjun; Kang, Zhiliang; Huang, Peng; Zou, Zhiyong; He, Yong; Yang, Ning; Peng, Yingqi; Dai, Jianwu; Wu, Zhijun; et al. (Frontiers in Plant Science, 2022)
Herein, a combined multi-point picking scheme was proposed, and the sizes of the end of bud-picker were selectively designed. Firstly, the end of bud-picker was abstracted as a fixed-size picking box, and it is assumed that the tea buds in the picking box have a certain probability of being picked. Then, the picking box coverage and the greedy algorithm were designed to make as few numbers of picking box set as possible cover all buds to reduce the numbers of picking. Further, the graham algorithm and the minimum bounding box were applied to fine-tune the footholds of each picking box in the optimal coverage picking box set, so that the buds were concentrated in the middle of the picking boxes as much as possible. Moreover, the geometric center of each picking box was taken as a picking point, and the ant colony algorithm was used to optimize the picking path of the end of bud-picker. Finally, by analyzing the influence of several parameters on the picking performance of the end of bud-picker, the optimal sizes of the picking box were calculated successfully under different conditions. The experimental results show that the average picking numbers of the combined multi-point picking scheme were reduced by 31.44%, the shortest picking path was decreased by 11.10% and the average consuming time was reduced by 50.92% compared to the single-point picking scheme. We believe that the proposed scheme can provide key technical support for the subsequent design of intelligent bud-picking robots.